Indoor exposure levels of ammonia in residences, schools, and offices in China from 1980 to 2019: A systematic review. (28th June 2021) - Sun, Chanjuan; Hong, Shijie; Cai, Guangkai; Zhang, Yinping; Kan, Haidong; Zhao, Zhuohui; Deng, Furong; Zhao, Bin; Zeng, Xiangang; Sun, Yuexia; Qian, Hua; Liu, Wei; et al.
Abstract: Indoor ammonia (NH3 ) pollution has been paid more and more attention in view of its health risk. However, few studies have investigated the exposure level in the non‐occupational environment in China. This study systematically reviewed the indoor ammonia exposure level in different regions, the equivalent exposure concentration of different populations, and the factors that influence indoor air ammonia in residences, offices, and schools in China. The literature published in 1980–2019 from main databases was searched and detailed screened, and finally, 56 related studies were selected. The results illustrated that the median concentration of indoor air ammonia in residences, offices, and school buildings was 0.21 mg/m 3, 0.26 mg/m 3, and 0.15 mg/m 3 . There were 46.4%, 71.4%, and 40% of these samples exceeding the NH3 standard, respectively. The national concentrations and the equivalent exposure levels of adults and children were calculated and found to be higher than 0.20 mg/m 3 . The concentration of ammonia varied greatly in different climate zones and economic development regions. Higher concentrations were found in the severe cold zone and the regions with higher economic level. This review reveals a high exposure risk of indoor air ammonia and the crucial impact of human emission, indoor air temperature, new concrete, and economic level, suggesting further investigation on indoor air ammonia evaluation and health effects.